Digital Image Forensic Approach to Counter the JPEG Anti-Forensic Attacks - Amit Kumar; Gurinder Singh; Ankush Kansal; Kulbir Singh (IEEE Access)
Rapid advancement in digital image processing tools and software’s has made it extremely simple to manipulate the digital images without leaving any footprints. It becomes a hot issue about the security and threat to society with increasing growth of social media. JPEG compression format has been widely used in most of the digital cameras. The investigation of JPEG compression footprints can play an important role in image tampering detection. In this paper, a novel method is proposed to detect the JPEG compression. The proposed forensic scheme comprises of two steps i.e. selection of target difference image and generation of second-order statistical features by evaluating the Markov Transition Probability Matrices (MTPMs) for both intra and inter-block DCT domain. Finally, the resultant feature is used to train the SVM classifier for classification purposes. The experiment results on UCID and BOSSBase datasets show that the proposed forensic technique based on MTPM is capable of detecting the JPEG compression traces even in the presence of anti-forensic attacks.